2014
DOI: 10.1186/s13048-014-0081-7
|View full text |Cite
|
Sign up to set email alerts
|

In vivo fate mapping of cryopreserved murine ovarian grafts

Abstract: BackgroundCryopreservation of ovarian tissue has been suggested as an alternative to restore fertility for ovarian failure before chemotherapy.MethodsOvaries of donor FVB/N-Tg (PolII–Luc) Ltc transgenic mice (n = 5) were cryopreserved and transplanted to the back muscles of recipient FVB/NJNarl wild-type mice that had undergone bilateral oophorectomy. We evaluated the fate of cryopreserved murine ovarian grafts by in vivo bioluminescent imaging (BLI), AMH mRNA expression and follicle counts.ResultsThere were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…[32] Chen et al [33] recently reported that ovarian cryopreservation by slow freezing compromises ovarian reserve by cryoinjury and ischemia, evident at an early stage after transplantation. Oktem et al [25] found that vitrified human ovaries have fewer primordial follicles and produce less anti-Müllerian hormone than slow-frozen ovaries.…”
Section: Discussionmentioning
confidence: 99%
“…[32] Chen et al [33] recently reported that ovarian cryopreservation by slow freezing compromises ovarian reserve by cryoinjury and ischemia, evident at an early stage after transplantation. Oktem et al [25] found that vitrified human ovaries have fewer primordial follicles and produce less anti-Müllerian hormone than slow-frozen ovaries.…”
Section: Discussionmentioning
confidence: 99%
“…The donors were 3-week-old immature male FVB/N-Tg (PolII-luc) Ltc transgenic mice with an H-2 haplotype (H 2 q ). These mice were created by the transgenic service of Level Biotechnology (New Taipei City, Taiwan), and the generation process was described in our previous studies [11,13,14]. In brief, after pronuclear microinjection of the PolII-Luc transgene into the FVB/N embryos, they could encode a 712-bp mouse RNA polymerase II promoter (PolII) and a modi ed re y luciferase cDNA (Promega pGL-2).…”
Section: Micementioning
confidence: 99%
“…As described in our previous study, we used FVB/N-Tg (PolII-luc) Ltc transgenic mice and showed that BLI is a viable tool for assessing the e cacy of germ cell transplantation in vivo in a transgenic male mouse model [11]. Our team has used this technology to track the survival of mouse ovarian iso-and allografts [12], the effects of immunosuppressant treatment after allotransplantation of ovarian grafts [13], and the fate of cryopreserved murine ovarian grafts [14]. These previous studies mainly focused on ovarian grafts since the BLI technology is rarely used in experiments for fertility preservation of ITT.…”
Section: Introductionmentioning
confidence: 99%
“…For example, embryo and egg freezing are not possible or are contraindicated in prepubertal females or those who cannot delay treatment for their primary condition (Jeruss and Woodruff 2009). For these patients, one experimental fertility option is ovarian tissue cryopreservation (OTC) (Backhus, et al 2007, Chen, et al 2014, De Vos, et al 2014, Dolmans, et al 2014, Ross, et al 2014, Stoop, et al 2014, Suzuki, et al 2015). OTC involves the removal of a whole ovary or cortical biopsies that are then cryopreserved by either slow freezing or vitrification (Rosendahl, et al 2011, Suzuki, et al 2015, Ting, et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…OTC involves the removal of a whole ovary or cortical biopsies that are then cryopreserved by either slow freezing or vitrification (Rosendahl, et al 2011, Suzuki, et al 2015, Ting, et al 2013). This tissue can be thawed at a later date and used to restore reproductive function (Backhus, et al 2007, Chen, et al 2014, De Vos, et al 2014, Dolmans, et al 2014, Ross, et al 2014, Stoop, et al 2014). OTC followed by orthotopic or heterotopic transplantation has resulted in restoration of endocrine function and fertility, with at least 60 live human births reported to date (Dittrich, et al 2015, Donnez and Dolmans 2015, Gamzatova, et al 2014, Smitz, et al 2010).…”
Section: Introductionmentioning
confidence: 99%